Прямі та обернені теореми наближених методів розв'язування абстрактної задачі Коші - Торба, С.М. (Український математичний журнал, 2007)
Рассмотрен приближенный метод решения задачи Коши для дифференциально-операторного уравнения, основанный на разложении экспоненты по ортогональным многочленам Лагера. Для начального значения конечной гладкости относительно оператора A доказаны прямая и обратная теоремы теории приближения в среднем, приведены примеры неулучшаемости соответствующих оценок в этих теоремах. Для целых векторов экспоненциального типа установлена экспоненциальная скорость сходимости, для классов Жевре — субэкспоненциальная, а также характеризация соответствующих классов в терминах скорости сходимости в среднем приближения. We consider an approximate method of the solution of the Cauchy problem for an operator-differential
equation based on the exponent decomposition in the orthogonal Lager polynomials. For the initial
value of finite smoothness with respect to the operator A, we prove direct and inverse theorems of the
theory of approximation in the mean and present examples of the unimprovability of corresponding
estimates in these theorems. We establish the exponential rate of convergence for exponential-type
entire vectors and the subexponential rate of convergence for the Gevrey classes. We also establish the
characterization of both classes of vectors in terms of convergence rate in the mean approximation.